Accuracy of intracranial pressure assessment with a non-invasive transcranial doppler and arterial blood pressure method in patients with suspected idiopathic intracranial hypertension - Nabil Al Shammas; Sophie Schumann; Dragana Köhler; Bernhard Rosengarten (The Ultrasound Journal, 2025)
Abstract Objective The incidence of idiopathic intracranial hypertension (IIH) has nearly doubled in the recent decade, possibly due to increasing obesity rates. Lumbar puncture pressure (LPP) assessment is still the diagnostic gold standard but due to invasiveness of the method, several non-invasive alternatives exist. We evaluated a non-invasive intracranial pressure (nICP) method for its accuracy to predict LPP. Methods Prospectively, we included patients with suspected IIH and obtained nICP by means of a combined bilateral transcranial Doppler and photoplethysmographic arterial blood pressure method. In addition, we searched for an empty sella sign by magnetic resonance tomography and evaluated the optical nerve sheath diameter (ONSD) bilaterally by Duplex sonography. We analyzed data on an individual level for their capability to predict LPP. Included were 70 patients from which 60 with a complete data set were used for further evaluation. Patients with symptomatic intracranial pressure were excluded. Results The nICP and LPP correlated with R = 0.85 on the right, and R = 0.79 on the left side (p < 0.001, respectively). The mean difference of nICP-LPP was 0.45 ± 4.93 cmH2O. Its sensitivity to predict an increased ICP was 0.92, the specificity was 0.88 and negative predictive value 0.88. The empty sella sign and the ONSD showed no significant correlation to the LPP. Conclusion The nICP method allows pre-diagnosis of increased ICP and might help in decision making for the need of LPP. Due to the moderately increased ICP levels, ONSD remained insignificant.